Unplanned Extubation in the NICU. Issue 2 (1st February 2013) - Barber, Jessica A.
ABSTRACT Unplanned extubation (UE) in the neonatal intensive care unit (NICU) is a significant patient safety and quality control issue. I describe the implementation of a quality improvement program using multifactorial prevention strategies, including staff education, identification of neonates at risk for UE, extubation and weaning, standardization of procedures, and comprehensive documentation. Additional research on quality improvement with strategies for neonates may prove beneficial in reducing UE rates in neonates.